American traitor the trial of Axis Sally [videorecording (Blu-Ray)] - Polish, Michael; Polish, Michael; Williams, Meadow, 1966-; Williams, Meadow, 1966-; Pacino, Al, 1940-; Norgaard, Carsten, 1963-; Owen, Vance, 1964-; Owen, Vance, 1964-; Owen, William E. (Lionsgate, 2021)
Tells the story of Mildred Gillars known as Axis Sally, an American actress employed by the Nazis to disseminate Axis propaganda during World War II.